Pemanfaatan Limbah Biogas Sapi sebagai Media Tanam Perbenihan Jambu Biji - Aryana Citra Kusumasari; Muryanto Muryanto (Universitas Sebelas Maret, 2019)
Cow biogas waste can be used as guava organic fertilizer. The objective of this research was to determine the composition of the planting media from biogas waste for the best guava seedling. This research was conducted in Ungaran Barat, Semarang, Central Java from July-December 2015. The method used was Randomized Complete Block Design (RCBD) one factor that is the ratio of media compositions of 5 treatments, 4 replications and 10 plants per treatment (200 polybag seedlings of citrus plants). The treatments tested were biagas waste at 0%, 11%, 20%, 27% and 33%. Parameters observed were plant height, stem diameter, number of leaves, number of fruits. The results showed that the higher the use of biogas waste as guava seedling media, the better the plant performance. The best media composition of biogas waste for guava seedling is 33% biogas waste organic fertilizer.